SrVO3-based anode materials for hydrocarbonfueledsolid oxide fuel cells - Macias Montiel, Javier (2017)
This work was focused on the assessment of SrVO3-based perovskites as prospective anodes for hydrocarbon-fueled solid oxide fuel cells or electrocatalysts for other fuel conversion processes. The main motivation was the known sulfur tolerance of vanadium-based oxide compounds, their inhibition of carbon deposition, when compared to metallic electrolacalysts, the stability of SrVO3 under very reducing conditions imposed by fuels, and its high electrical conductivity when compared with alternative perovskite materials proposed for conversion of hydrocarbons. Yet, processing conditions require reducing conditions for synthesis and firing of singlephase SrVO3, due to the limited tolerance to oxidizing conditions. Limited redox tolerance also raises doubts about its ability to operate under conditions of high fuel conversion, and to allow discontinuous operation and interruption of operating conditions (intermediate or relatively high temperatures and reducing atmospheres) for maintenance or due to unexpected shutdown. Thus, the main objective was to develop SrVO3-based materials with extended tolerance to relatively inert or oxidizing atmospheres, without excessive penalty for electrical conductivity and other relevant properties, seeking applicability as fuel electrodes or electrocatalysts. One also considered the development of alternative SrVO3-based materials with greater flexibility for processing as electrodes or electrocatalysts in contact with SOFC electrolytes. Relations between the stability of SrVO3-based materials and redox conditions imposed by fuels are overviewed in Chapter I, based on relevant literature, and then re-examined by thermodynamic analysis of gradual fuel conversion and corresponding materials stability ranges (Chapter II). This also emphasizes the impact of Sr:V activity ratio on stability of the SrVO3-based perovskite phase, and provides guidelines to prevent onset of unwanted secondary phases by composition changes. Experimental evidence confirmed that the most common secondary phases are the pyrovanadate Sr2V2O7, promoted by oxidizing conditions, and/or the orthovanadate Sr3V2O8, which is most likely by a combination of oxidizing conditions and high Sr:V activity ratio. Thus, their inferior transport properties, relative stability, and other relevant properties (e.g. thermochemical expansion) were studied in detail in Chapter III, and compared with corresponding properties of the SrVO3 perovskite. Composition changes and corresponding impact on redox stability and metastability, defect chemistry, transport properties, thermochemical expansion and other relevant properties of SrVO3-based perovskites were studied in Chapters IV and V. The design of these compositions was guided by thermodynamic analysis of the impact of Sr:V activity ratio and redox conditions on stability, combined with guidelines provided by the dependence of tolerance factor of (Sr1-xAx)(V1-yBy)O3+d compositions on partial substitutions in both sites, i.e., A = La, Y and B = Nb. Thermodynamic predictions and the tolerance factor were also guidelines to design compositions and redox conditions required to obtain single phase Sr(V,Ti)O3-d materials and corresponding 2-phase materials with separate Ti-doped SrVO3 and V-doped SrTiO3 phases, as described in Chapter VI. This chapter includes a detailed study of processing conditions for flexible phase design, and also the relevant impact on stability, transport properties, thermochemical expansion, and transient responses to thermal or redox cycling. Those detailed studies reported mainly in Chapter VI, combined with guidelines from Chapters IV and V, provided the required information for the preparation of half cells and preliminary electrochemical tests, reported in Chapter VII; this includes: i) reactivity between SrVO3-based materials and solid electrolytes (YSZ and CGO), ii) deposition of electrodes onto YSZ electrolyte, with or without CGO buffer layer, and preliminary electrochemical screening. Effects on polarization resistance emphasize significant differences between single-phase Sr(V,Ti)O3-d and 2-phase SrVO3-SrTiO3 electrodes, demonstrate the role of CGO buffer layers, and suggest major impact of microstructural effects, ascribed to processing.